Pengaruh Brand Image, Social Media Instagram dan Beuaty Influencer Terhadap Keputusan Pembelian Produk Ms Glow di Kabupaten Lamongan - Yunni Rusmawati DJ; Emalia Nova Sustyorini (UNIVED Press, 2022)
The purpose of this research is to know the Brand Image, Beuaty Influencer and Social Media Instagram have an influence on purchasing decisions. Consumers who want to buy and use MS Glow products in Lamongan are the population in this study. Sampling using nonprobability sampling technique by taking a sample of 100 respondents. This research is a quantitative research. Based on the results of the t test, Brand Image states that it has a positive and significant effect on purchasing decisions, while there is no positive and significant effect on Beuaty Influencers onSocial Media Instagrampurchasing decisions ,, has a positive and significant effect. Meanwhile, when tested with the N test, the F Brand Image, Beuaty Influencer and Social Media Instagram simultaneously had a positive and significant effect on purchasing decisions.